Determinants of GRI-based sustainability reporting: evidence from an emerging economy. Issue 1 (12th September 2019) - Orazalin, Nurlan; Mahmood, Monowar
Abstract : Purpose: The purpose of this paper is to investigate the extent and determinants of sustainability performance disclosures reported by publicly traded companies in Kazakhstan by using the Global Reporting Initiative (GRI) framework. Among the different possible determinants, stand-alone sustainability reporting (SR), reporting language, leverage, cash flow capacity, profitability, size, age and auditor type were selected to investigate their impacts on the quality and scope of sustainability information. Design/methodology/approach: The study analyzes data from publicly traded companies at the Kazakhstani Stock Exchange for the years 2013–2015. To investigate the extent, nature and quality of sustainability reports, the study measures and analyzes economic, environmental and social performance parameters, as suggested in the GRI guidelines. Findings: The results indicate that determinants such as stand-alone reporting, reporting language, firm profitability, firm size and auditor type substantially influence the extent, nature and quality of sustainability-reporting practices of Kazakhstani companies. Practical implications: The findings of the study suggest that managers, practitioners, regulators and policy makers in emerging economies should adopt the GRI guidelines to report sustainability performance disclosures and focus on specific factors to improve the quality of sustainability disclosures. Originality/value: This study is one of the first studies to investigate the extent, nature and possible determinants of corporate SR in central Asian-emerging economies.